A Counterfactual Analysis of the Progressive - Varasdi, Károly (Proceedings of the Amsterdam Colloquium, 2003)
The approach presented in this paper1 sees the basic problem of the progressive aspect as one of identifying the truth-makers of progressive sentences.2 One of the basic tenets of the truth-maker approach is that truth supervenes on reality, ie., that the truth-value of a proposition is somehow determined by what exists. The question of what types of truth-makers there are or may possibly be is still fairly controversial but there seems to be consensus that situations should be among them. In the case of the progressive this boils down to the question of describing those situations that make a progressive sentence true, false, or undefined. An especially flexible framework for theorizing about situations and their relation to natural language is Lenhart Schubert's FOL** formalism developed in [10], which will be used in this paper as a general framework for the analysis.